The Conformation of the Prion Domain of Sup35 p in Isolation and in the Full‐Length Protein1. Issue 48 (9th October 2013) - Luckgei, Nina; Schütz, Anne K.; Bousset, Luc; Habenstein, Birgit; Sourigues, Yannick; Gardiennet, Carole; Meier, Beat H.; Melki, Ronald; Böckmann, Anja
<x xml:space="preserve">Abstract</x> The whole is not the sum of the parts: Fibrils form both from the full‐length Sup35 prion protein and also from its isolated NM domain. A conformation analysis of both shows that Sup35NM and fragments thereof, which are often used as convenient models for prion fibril assembly, have a very different conformation of the prion domains.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>